Enhancing Efl Learners Motivation Through Physical Activities : A Study In MTS YMPI Rappang - Syahrir, Haikal; T, Syamsu; Aisa, Sitti; Hermansyah, Sam (Universitas Muhammadiyah Enrekang, 2026)
This study aimed to investigate how physical activities enhance EFL learners’ motivation in learning English at MTs YMPI Rappang. The research focused on identifying the types of physical activities that effectively increased students’ motivation and exploring the challenges encountered during their implementation in the classroom. Physical activities such as Total Physical Response (TPR), movement-based games, and role-playing were integrated into English lessons to create a more interactive and engaging learning environment. This research employed a descriptive qualitative design supported by quantitative data from questionnaires. The participants consisted of ninth-grade students at MTs YMPI Rappang and one English teacher. The data were collected through classroom observation, semi-structured interviews, questionnaires, and documentation. The qualitative data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, while the questionnaire data were analyzed using descriptive statistics. The findings revealed that the integration of physical activities significantly improved students’ motivation, participation, and confidence in learning English. Students showed higher enthusiasm, were more actively involved in classroom activities, and demonstrated greater willingness to communicate during the learning process. Physical activities also created a more dynamic classroom atmosphere and reduced students’ anxiety toward learning English. However, several challenges were identified, including classroom management, time limitations, and differences in students’ learning styles. the use of physical activities in EFL classrooms positively contributes to enhancing students’ motivation and engagement in learning English. Therefore, integrating movement-based strategies into English instruction is recommended as an effective approach to create more interactive and motivating learning experiences.